Physicochemical analysis of Ugandan tea (Camellia sinensis) germplasm reveals potential commercial green and black tea varieties - Grace Nalugo, Racheal; Kaweesi, Tadeo; Kawooya, Ronald; Nuwamanya, Ephraim; Mugisa, Charles; Namutebi, Vivian; Tumwine, Venansio; Turyahebwa, Vereriano; Tumuhimbise, Robooni (Taylor & Francis, 2023)
Tea (Camellia sinensis L.) is an important beverage consumed worldwide. In Uganda, it is the second-largest and highly priori-tized export crop after coffee and provides the much-needed jobs to more than 800,000 people. Despite its importance in the coun-try, the crop has received very limited research attention for its improvement and optimal utilization. This study was aimed at characterizing existing tea germplasm in Uganda to inform future breeding initiatives for market-preferred tea varieties. Fifty-eight advanced tea clones were randomly selected from the tea germ-plasm conserved at Uganda’s Tea Research Center in Rwebitaba and analyzed in the laboratory for eight physicochemical descrip-tors. Hierarchical cluster analysis performed on the 58 clones using Cluster-R package revealed four main clusters, indicating the exis-tence of variation for physicochemical parameters within tested germplasm. This variation can be exploited to select among and/or improve the studied germplasm genetically for quality. High fer-mentation rate, which is one of the key indicators for good-quality black teas, revealed 15 fast-fermenter tea clones. Clone “UTR12/12” was identified as the most rapid fermenter, fully fermenting within 30 min, which implies a good clone for black tea. The clone also had the highest polyphenol content (26.7%), higher than the high- quality clone “UTR6/8” (control). Other tea clones whose polyphe-nol content was within the range of the control black tea clone were: “UTR144/10” (20.9%) and ‘UTR144/17, (20.66%). The identi-fied promising black tea clones can be advanced to multi-location trials for further evaluation and selection for eventual variety release as commercial black-tea clones.
Keywords: Black tea; camellia sinensis; germplasm characterization; green tea; physicochemical parameters; tea quality1IntroductionTea (Camellia sinensis L.) is the second most widely consumed beverage in the world after water (Patel et al. 2019). Its demand is influenced by briskness, liquor, aroma, and taste-quality aspects (Mukhtar and Ahmad 2000). TheCONTACT Robooni Tumuhimbise rtumuhimbise@hotmail.com Tea Research Centre, Rwebitaba Zonal Agricultural Research and Development Institute, Fort Portal 7084, Kabarole, Uganda†These authors have contributed equally to this work and share first authorshipJOURNAL OF CROP IMPROVEMENT2023, VOL. 37, NO. 3, 341–360https://doi.org/10.1080/15427528.2022.2095317© 2022 Informa UK Limited, trading as Taylor & Francis Group